What a Load of Rubbish! : Rescue Your Household Waste, It's Worth More than you Think! - Skidmore, Steve (London Cassell Publishers Ltd, 1990)
Draws attention to the quanitity and content of household rubbish and suggests ways of reducing and recycling it.
Include Color Illustration and Index
Keywords: Recycling (Waste, etc.) -- Refuse and refuse disposal -- Environmental protection